Failure of roof truss due to extreme wind in Malaysia : a study on consultant perspective - Nurul Huda, Azizan (2014)
High wind speeds pose a threat to the integrity of structures, particularly those at exposed sites such as roof truss structure. In any design project for especially for tall structures, accurate estimation of the occurrence of extreme wind speeds is an important factor in achieving the correct balance. The case reported in the Sinar Harian on 1 October 2013, severe damage of properties happen because of the roof truss that made from 65 meters iron at Supermarket Xiri that located at Batu 2 Jalan Kuala Berang was collapsed due to extreme wind. Other than that, Harian Metro also reported the same incident that happened in Kampung Manjoi, Perak on 11 May 2013 at 6.45 PM which is at least about 23 houses damages due to strong wind especially in the roof structure. The major problems that cause this roof failure will be investigate especially on consultant perspective whether the mistake comes from the calculation in design stage or from the construction materials or construction methods that have been implemented over these years. The main objectives of this research is to investigate the roof structure system that frequently fails during extreme wind event and also to determines the problems of the roofing system under extreme wind load in accordance with Malaysian consultation industry practices. For this study, it is taken on the combined quantitative and qualitative approach of research with the use of the survey questionnaire and published literatures. With base SPSS, data collection that get from Google Doc can be manage with case selection, file reshaping, and creating derived data and this research will able to obtain the advantages of both quantitative and qualitative approaches and overcome their limitations. By doing analysing and data findings using SPSS, the result clearly shows the causes of roof truss failure due to extreme wind in Malaysia, the roof truss design consideration and also some effective methods to overcome the problem of roof truss failure due to extreme wind in Malaysia. Determination of the failure whether in design stage or others consultant factors have been done and it can be conclude that the failure is not comes from the design stage but it is comes from the other consultant factors. There are four recommendations which is undertake research to improve the understanding of extreme wind loadings, develop guidelines for the design of roof structures subject to extreme wind loadings, mandatory levels be set for independent third party design review and construction monitoring assisted by appropriately qualified people and structural engineers be required to identify on the drawings collapse critical components of important roof structures subject to extreme wind loading. The research effort produced valuable outcomes that become a references and basis for the study regarding to wind disaster.